Full-Squat as a Determinant of Performance in CrossFit - Martínez-Gómez, Rafael; Valenzuela, Pedro L.; Barranco-Gil, David; Moral-González, Susana; García-González, Adela; Lucia, Alejandro (International Journal of Sports Medicine, 2019)
This study analyzed the relationship between CrossFit performance and power and strength variables measured in the full-squat exercise. Twenty male trained subjects (33±7 years) performed an incremental load full-squat test for assessment of the 1-repetition maximum (1RM) and the mean (Pmean) and peak (Ppeak) power. Performance in 5 different Workouts of the Day (WODs) was measured on different days, and overall CrossFit performance was determined as the sum of the scores obtained in these WODs. Athletes were then assigned to a high (HP) or low (LP) performance group based on the median score for overall performance. Correlation analysis between squat variables and performance was performed and between-group differences were assessed. Moderate to strong (r=0.47–0.69, p<0.05) positive correlations were found between squat variables and performance in the different WODs. Overall CrossFit performance was strongly and positively associated with absolute (r=0.62, p=0.01) and relative 1RM (r=0.65, p=0.07), and relative Pmean (r=0.56, p=0.02) and Ppeak (r=0.53, p=0.03). Large differences (effect sizes ranging 1.1–1.7, all p<0.05) were observed between HP and LP for absolute and relative 1RM, relative Pmean, and absolute and relative Ppeak. In summary, strength and power indexes measured in a squat test are positively associated with CrossFit performance.
Keywords: assessment; resistance exercise; strength; power